ANALISIS PENDAPATAN PETANI KARET DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA TEMPAPAN HULU KECAMATAN GALING PERSPEKTIF EKONOMI ISLAM - Nuriani; Hutagaluh, Oskar; Jum’an (Cross-Border Journal of Business Management, 2025)
The development of the agricultural sector is directed at increasing the productivity of agricultural products to meet the food needs of the people and the needs of the domestic industry, increase exports, increase farmer incomes, expand employment opportunities and encourage business opportunities. In Galing District, most of the people's livelihoods are farming, planting plantation commodities such as rubber. Technically the commodities in Galing District are very supportive, there is still a lot of unused critical land which is a potential for plantation development in the future. One of them is that in Tempapan Hulu Village almost every household in Tempapan Hulu Village works as a rubber farmer. Even though Tempapan Hulu Village is one of the rubber-producing villages in Galing District, the reality shows that not all rubber farming communities live in better conditions and with the same land area but there are different levels of income generated by rubber farmers. This research is a field research with primary data and secondary data. Collecting data in this study using the method of observation, interviews. The analytical method used is a qualitative analysis method. The results of this study indicate that the income level of the community in Tempapan Hulu Village is still relatively low because the income of the people who still do not meet the UMK standards of Sambas Regency, the income of the rubber farming community is only around 1-2 million due to low rubber prices and also the rubber farmer's income depends on the weather . For the welfare of the community in Tempapan Hulu Village it is also still relatively low because the income from rubber products has not been able to fully meet the needs of the community and also the education of the community is still low due to damaged road access and also schools that are not provided in the village while for welfare in an economic perspective Islamic society belongs to the perspective of Islamic economics because the community carries out it responsibly and involves Allah in the work and also they perform the dawn prayer first before tapping rubber and in buying fertilizer the community has paid in cash not in debt.